Direct Detection and Quantification of Bacterial Cell-free DNA in Patients with Bloodstream Infection (BSI) Using the Karius Plasma Next Generation Sequencing (NGS) Test. (4th October 2017) - Wanda, Lisa; Ruffin, Felicia; Hill-Rorie, Jonathan; Hollemon, Desiree; Seng, Hon; Hong, David; Blauwkamp, Tim; Kertesz, Mickey; Fowler, Vance
Abstract: Background: Blood cultures can have low sensitivity if a patient is pretreated with antibiotics. A molecular diagnostic for bloodstream infection (BSI) that can also quantitate pathogen DNA could be a useful tool in detecting and monitoring culture-negative infections. Methods: We prospectively enrolled 75 patients (50 with culture confirmed BSI due to Staphylococcus aureus [ n =  21] or Gram-negative bacilli [ n =  29] at baseline, and 25 with negative blood cultures) to evaluate the Karius plasma next generation sequencing (NGS) test to detect BSI. Blood samples from patients with confirmed BSI were collected for the study within one day of positive blood culture and then every 2–3 days. Cell-free DNA (cfDNA) was extracted from plasma and underwent NGS in the Karius CLIA/CAP laboratory (Redwood City, CA). After removal of human sequences, remaining reads were aligned against a curated pathogen database. Organisms present at a significance-level above a predefined threshold were reported. Quantity of cfDNA for each reported pathogen was expressed as molecules per microliter (MPM). Results: When compared with baseline blood culture, the plasma NGS test had a positive agreement of 80% (40/50) and negative agreement of 84% (21/25). Overall, serially collected samples were positive by plasma NGS testing significantly longer than blood culture (mean 6.0 days vs. 2.4 days, respectively; P  < 0.0001. Figure). Patients with BSI were positive longer by NGS testing than blood culture for both S. aureus (mean 6.9 days vs. 4.0 days, respectively; P  < 0.005) and gram-negative bacilli (mean 5.4 days vs. 1.3 days, respectively; P  < 0.001). Pathogen cfDNA in BSI patients, quantified as MPM, declined over time during treatment. S. aureus MPM declined more slowly than gram-negative MPM and was significantly higher than gram-negative MPM at day 6 ( P  < 0.001). Conclusion: The Karius plasma NGS test can directly detect pathogens in patients with BSI. Pathogen cfDNA signal in plasma remains positive longer than blood culture and combined with quantification of pathogen cfDNA, could be a useful biomarker to aid in diagnosis and monitoring of infections, particularly in those with sterile blood cultures. Disclosures: L. Wanda, Karius, Inc: Collaborator and Employee, Salary; F. Ruffin, Karius, Inc.: Collaborator and Research Contractor,  Salary; J. Hill-Rorie, Karius, Inc: Collaborator, Research support and Salary; D. Hollemon, Karius, Inc: Employee, Salary; H. Seng, Karius, Inc: Employee,  Salary; D. Hong, Karius, Inc.: Employee,  Salary;  T. Blauwkamp, Karius, Inc: Employee,  Salary; M. Kertesz, Karius, Inc: Employee,  Salary; V. Fowler Jr., Karius, Inc: Grant Investigator, Grant recipient Pfizer, Novartis, Galderma, Novadigm, Durata, Debiopharm, Genentech, Achaogen, Affinium, Medicines Co., Cerexa, Tetraphase, Trius, MedImmune, Bayer, Theravance, Cubist, Basilea, Affinergy, Janssen, xBiotech, Contrafect: Consultant, Consulting fee NIH, MedImmune, Cerexa/Forest/Actavis/Allergan, Pfizer, Advanced Liquid Logics, Theravance, Novartis, Cubist/Merck; Medical Biosurfaces; Locus; Affinergy; Basilea; Contrafect; Karius: Grant Investigator, Grant recipient Green Cross, Cubist, Cerexa, Durata, Theravance; Debiopharm: Consultant, Consulting fee UpToDate: Royalties, Royalties